2021
DOI: 10.31851/hon.v4i2.5239
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Level Effect On The Grade-Point Average Of Physical Education Major Students

Abstract: This study aims to percieve the relationship between physical fitness and the grade-point average. This study used a quantitative method with survey techniques with design correlation. The subjects of this study were 1st and 3rd semester physical education college students with total sample of 142 students (M: 97, F: 45). Random sampling was used as the sampling technique and TKJI (Indonesian Physical Fitness Test) was used as the instrument in this study was. The results show that 4 students (2,82%) were in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Physical fitness and health are needed by students to enhance their learning abilities and complete other assignment, so that educational goals will be achieved. In addition, according to a recent study reported that physical fitness is also useful for living life and if someone has low physical fitness, then that person will easily get tired in carrying out daily activities (Bayu et al, 2021). Some studies have reported the decreasing physical fitness after 8 to 12 weeks of inactivity (Setiawan, Iwandana, Festiawan, & Bapista, 2020;Patah, Jumareng, Setiawan, Aryani, & Gani, 2021 efforts that can be made so that children's physical fitness continues to improve by providing 2012 physical fitness exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Physical fitness and health are needed by students to enhance their learning abilities and complete other assignment, so that educational goals will be achieved. In addition, according to a recent study reported that physical fitness is also useful for living life and if someone has low physical fitness, then that person will easily get tired in carrying out daily activities (Bayu et al, 2021). Some studies have reported the decreasing physical fitness after 8 to 12 weeks of inactivity (Setiawan, Iwandana, Festiawan, & Bapista, 2020;Patah, Jumareng, Setiawan, Aryani, & Gani, 2021 efforts that can be made so that children's physical fitness continues to improve by providing 2012 physical fitness exercises.…”
Section: Introductionmentioning
confidence: 99%